The deal of a lifetime [compact disc, unabridged] : a novella - Backman, Fredrik, 1981- (Simon & Schuster Audio, 2017)
Fredrik Backman returns with a profound and moving novella set on Christmas Eve about the intertwining destinies of a man who has built a global empire, but lost his family in the process, and a courageous little girl fighting for her life.